Safety Research On Workers At Construction Site - Paul Teh, Ou Yang (Universiti Sains Malaysia, 2005)
The construction industry has always been one of the main sectors to boost Malaysia’s economy and it will help to steer Malaysia into year 2020. However, before we can take pride of that achievement, we must take note of the lagging safety record in the construction industry. The website of Department of Occupational Safety and Health (DOSH) has records of occupational accidents which happened in recent years (refer to Appendix A). These accidents happened due to poor safety practices and human factors. Occurrence of such tragedies should never be regarded as necessary consequences of development and advancement. Instead, the major problems such as ignoring safety guidelines, carelessness, indiscipline and lack of supervision should be tackled. If strict standards have been set, enforcement has been carried out and procedures and regulations have been adhered to, the rate of accidents will definitely be reduced. Besides that, loss of lives could be avoided and financial losses could be cut. Therefore, this research will discuss the main factor of accident occurrences – HUMAN FACTOR and analyzes the various regulative institutions involved in occupational safety. It also studies the construction safety practices which will help to reduce the rate of accidents. These safety practices includes personal protective equipment, emergency response, fire protection and prevention, signs and barriers, scaffold, piling, cranes and excavation. Lastly, there are some suggestions in this thesis which might serve as good solutions to reducing accident occurrences. It is worth noting that all the players in this industry should always be sensitive towards this problem. They should cooperate and take necessary measures at site to resolve the problem.